Analysis of Marketing Channels and Price Effect to Rice Marketing Efficiency in Aceh, Indonesia - Yunus, Mukhlis; Syahputra, Hendra (Jurnal Manajemen Teknologi, 2013)
The objective of this study is to empirically explore the influence of marketing channels and price to rice marketing efficiency in Aceh Province, Indonesia. Six hundreds farmers' households from six districts of rice production base in Aceh were selected for the samples and analysed using the structural equation modelling (SEM). This study has been successfully documented how inefficient was the marketing of rice in Aceh because the farmers still tended to choose higher level of marketing channel with lower marketing performance. The price of rice was unstable, especially during the harvest and famine seasons, despite the government having set up a price policy. This study also found that marketing channels had positive and significant relationship with the rice marketing efficiency.Keywords: Efficiency, Marketing, Prices, Rice Marketing Channels, Price Effect